Comparative study of the digital design status of cultural heritage on China’s Grand Canal and Europe’s Danube river - Jing Zhao; Yiming Ma; Yuhong Han; Duoliya; Branislav Antonić (Conservation Science in Cultural Heritage, 2025)
This paper conducts a comparative analysis of the digital design status of cultural heritage in two historically significant waterways: the Grand Canal in China and the Danube River in Central Europe. It investigates the current state of digitalization, the technological methods employed in digital design, and the forms of revitalization. Through a comprehensive comparative analysis, the study emphasizes key distinctions in sustainable concepts, technological applications, experience design, and social management service design. Furthermore, it identifies common features and shared challenges faced in both waterway regions. This research offers valuable insights into the digital preservation and activation of cultural heritage in these vital waterways, promoting cultural exchange between China and Europe and enhancing the global renewal of cultural heritage in ancient river basins.